Effects of natural Lithium and Lithium isotopes on voltage gated sodium channel activity in SH-SY5Y and IPSC derived cortical neurons - Bukhteeva, Irina; Livingstone, James D.; Singh, Kartar; Pavlov, Evgeny V.; Beazely, Michael A.; Gingras, Michel J. P.; Leonenko, Zoya (Springer Nature, 2025)
Although lithium (Li) is a widely used treatment for bipolar disorder, its exact mechanisms of action remain elusive. Research has shown that the two stable Li isotopes, which differ in their mass and nuclear spin, can induce distinct effects in both in vivo and in vitro studies. Since sodium (Na+) channels are the primary pathway for Li+ entry into cells, we examined how Li+ affects the current of Na+ channels using whole-cell patch-clamp techniques on SH-SY5Y neuroblastoma cells and human iPSCderived cortical neurons. Our findings indicate that mammalian Na+ channels in both neuronal models studied here display no selectivity between Na+ and Li+, unlike previously reported bacterial Na+ channels. We observed differences between the two neuronal models in three measured parameters ( Vhalf , Gmax, z). We saw no statistically significant differences between any ions in SH-SY5Y cells, but small differences in the half-maximum activation potential ( Vhalf ) between Na+ and 6Li+ and between 7Li+ and 6Li+ were found in iPSC-derived cortical neurons. Although Na+ channels are widely expressed and important in neuronal function, the very small differences observed in this work suggest that Li+ regulation through Na+ channels is likely not the primary mechanism underlying Li+ isotope differentiation.
Keywords: Lithium isotopes; Mammalian sodium channels; IPSC-derived cortical neurons; SH-SY5Y; Patch-clamp